Seroprevalence of Anti-SARS-CoV-2 Antibodies in a Random Sample of Inhabitants of the Katowice Region, Poland - Zejda, Jan E.; Brożek, Grzegorz M.; Kowalska, Małgorzata; Barański, Kamil; Kaleta-Pilarska, Angelina; Nowakowski, Artur; Xia, Yuchen; Buszman, Paweł (International journal of environmental research and public health, 2021)
Lack of knowledge around seroprevalence levels of COVID-19 in Poland was the reason for the implementation of a seroepidemiological study in the Katowice Region (2,100,000 inhabitants). In October–November 2020, a questionnaire examination and measurement of anti-SARS-CoV-2 IgG and IgM antibodies were performed in a random sample of the general population (n = 1167). The objectives of the study were to estimate the prevalence of IgG and IgM antibodies and to assess their host-related correlates. The prevalence of IgG seropositivity was 11.4% (95% CI: 9.5–13.2%) and IgM seropositivity was 4.6% (95% CI: 3.5–5.8%). Diagnosis of COVID-19 was found in 4.8% of subjects. A positive IgG test was statistically significantly associated with age (inverse relationship), a person’s contact with a COVID-19 patient, quarantine, and two symptoms in the past: fever and loss of smell/taste. Positive IgG tests were less prevalent in subjects who had diagnoses of arterial hypertension, diabetes, or rheumatologic disorders. IgM test positivity was associated with quarantine and loss of smell/taste only with no effect of chronic diseases found. In Poland, in the period October–November 2020, the prevalence of SARS-CoV-2 infection was larger than earlier estimates obtained in other European countries, probably reflecting the measurements obtained during the “second wave” of the epidemic.